Being, nature, and life in Aristotle essays in honor of Allan Gotthelf - Lennox, James G.; Bolton, Robert (Robert A. N.) (Cambridge University Press, 2010)
"This volume of essays explores major connected themes in Aristotle's metaphysics, philosophy of nature, and ethics, especially themes related to essence, definition, teleology, activity, potentiality, and the highest good. The volume is united by the belief that all aspects of Aristotle's work need to be studied together if any one of the areas of thought is to be fully understood. Many of the papers were contributions to a conference at the University of Pittsburgh entitled 'Being, Nature, and Life in Aristotle', to honor Professor Allan Gotthelf's many contributions to the field of ancient philosophy; a few are contributions from those who were invited but could not attend. The contributors, all longstanding friends of Professor Gotthelf, are among the most accomplished scholars in the field of ancient philosophy today"--